2020
DOI: 10.1128/aac.02261-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MIC Test Strip and Sensititre YeastOne with the CLSI and EUCAST Broth Microdilution Reference Methods for In Vitro Antifungal Susceptibility Testing of Cryptococcus neoformans

Abstract: We compared MIC test strip (MTS) and Sensititre YeastOne (SYO) methods with EUCAST and CLSI methods for amphotericin B, 5-fluocytosine, fluconazole, voriconazole, and isavuconazole against 106 Cryptococcus neoformans isolates. The overall essential agreement between the EUCAST and CLSI methods was >72% and >94% at ±1 and ±2 dilutions, respectively. The essential agreements between SYO and EUCAST/CLSI for amphotericin B, 5-flucytosine, fluconazole, and voriconazole were >89/>93% and between MTS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Jesu’s Guinea 22 reported that Sensititre YeastOne was suitable for the analysis of A. fumigatus itraconazole and voriconazole MICs when results were assessed at 48 h of incubation. Fatima Zohra Delma 23 reported essential agreement between Sensititre YeastOne and EUCAST/CLSI for amphotericin B, 5-flucytosine, fluconazole, and voriconazole with >89%/>93% for MTS and for EUCAST/CLSI 57%/>75%. Major error rates are low for amphotericin B and fluconazole (<3%) and a bit higher for the other drugs (<8%).…”
Section: Discussionmentioning
confidence: 96%
“…Jesu’s Guinea 22 reported that Sensititre YeastOne was suitable for the analysis of A. fumigatus itraconazole and voriconazole MICs when results were assessed at 48 h of incubation. Fatima Zohra Delma 23 reported essential agreement between Sensititre YeastOne and EUCAST/CLSI for amphotericin B, 5-flucytosine, fluconazole, and voriconazole with >89%/>93% for MTS and for EUCAST/CLSI 57%/>75%. Major error rates are low for amphotericin B and fluconazole (<3%) and a bit higher for the other drugs (<8%).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, a new low-cost four-well plate agar method is suitable for echinocandin susceptibility screening of Aspergillus species and can be used to detect echinocandin non-WT isolates [ 185 ]. Moreover, MIC test strip and Sensititre YeastOne showed an overall agreement of >72% and >94% at ±1 and ±2 dilutions when compared to CLSI and EUCAST broth microdilution methods, respectively [ 186 ].…”
Section: Antifungal Susceptibility Testing: Current Paradigm Chalmentioning
confidence: 99%
“…Second, we recommend comparing the MICs to existing MIC distributions for that drug and species to determine if the MIC is most likely "normal" or "elevated" (indicating possible acquired resistance). In Tables 4-7, we summarised our data for more than 4000 isolates and documented alignment to published EUCAST data [25,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] (for details on this data, see Supplementary Text S2). These tables can be used for comparison if the local susceptibility testing is confirmed to align with EUCAST testing.…”
Section: General Considerationsmentioning
confidence: 99%